Realidade social e opressão no discurso de Vidas Secas, de Graciliano Ramos - Varjão, Nadia Cristina (2012)
This work aims study the social reality portrayed in the regionalist novel Vidas Secas, by Graciliano Ramos, marked in the regional history of the backland, and pointing to the marks of oppression against backland people present in the discursive production of the novel. The focus on the social reality, presented by the report of the history of droughts in the Northeast, is fundamentally brought by Villa s studies (2001), followed by notes of historiographical basis that consider Literature as likely to be historical source. Then we elucidate the social commitment present in this generation of writers in the end of nineteenth and the beginning of twentieth centuries, highlighting the political positioning of Graciliano Ramos. Based on the theoretical Critical Discourse Analysis (CDA) in its approach from Fairclough (2001), we analyze the meanings of words that point to traces of oppression resulting from discourses of social matrices and, further, we analyzed the projection of the social ethos of the characters from the perspective of social oppression, revealed in interdiscursive level and submitted to existing orders of discourse. The research enabled us to observe social practices prevalent in Brazilian backlands, proven by historical records and high degree of oppression against backland people constituted in discourse Graciliano that, in turn, has always shown a commitment to uncover the man of his time under the imprint of maladjusted and socially unequal realities